Comparison of propagation methods of different moss species used as wall and ground covering ornamental plants - Ónody, É.; Fülöp-Pocsai, B.; Tillyné Mándy, A.; Papp, B.; Tóth, E.; Ördögh, M. (International Journal of Horticultural Science, 2016)
Mosses are traditionally used as ornamental plants, especially in Japan, USA, England (moss gardens) and Germany, French (green roofs). In shadow areas (where the members of Poaceae usually cannot grow well), mosses are potentially use as “grass”. The stocks of moss colonies maintain optimal microclimate and decrease desiccation of soils (like mulch). Additionally, mosses are evergreen, attractive all year, during winter. In our study, 18 moss species were propagated by fragments (as mixture, with the use of 16 species) and transplantation of carpets (with Brachythecium rivulare and Calliergonella cuspidata) in Szentendre. The aim was to find the most durable species and the best way of propagation. In an outdoor, irrigated garden, propagation by fragments was effective (with 63% coveration) and higher values (93% and 76%) were obtained in the cases of non-irrigated stocks of Amblystegium serpens (in trays) and moss carpets. In vertical structures (moss picture-frames with the use of mixtures), protonema of 2 species (Hypnum cupressiforme and Eurhynchium hyans) covered 24 and 33% of the 0.5 x 0.5 m sized area.